Directed Magnesiation of Polyhaloaromatics using the Tetramethylpiperidylmagnesium Reagents TMP2Mg⋅2 LiCl and TMPMgCl⋅LiCl. Issue 8 (15th May 2013) - Unsinn, Andreas; Rohbogner, Christoph J.; Knochel, Paul
Abstract: A convenient and efficient functionalization of polyhaloaromatics via regioselective magnesiation has been developed. Starting from simple, inexpensive but structurally challenging arenes, metallation by magnesium amide bases was achieved under mild conditions. The desired Grignard reagents were stable towards aryne formation, were obtained in good yields within short reaction times and could be reacted with a variety of typical electrophiles, providing attractive, functionalized building blocks in good to excellent yields. As an application we have prepared the antimicrobial natural product 2, 6‐dichloro‐3‐phenethylphenol isolated from the New Zealand liverwort Riccardia marginata . This synthesis involves a mixed bimetallic compound prepared via metallation of a phenylboronic acid pinacol ester derivative and subsequent selective cross‐coupling. Abstract :